Taxonomic studies on the genus Crassula L - Tolken, H R (Department of Biological Sciences, 2016)
The difficulties involved in the taxonomy of the genus Crassula, such as the extensive variation and often difficult species complexes, vicariousness and hybridization, are sketched against a historical background. These difficulties have prompted the author to review concepts of taxa from subspecific to generic level and have also led to the approach adopted in this work. It is argued that in several genera and sections, as previously recognized, too much stress was placed on the several floral characters which form part of a pollination syndrome which is shown up by convergent developments of these flower types. The different types of seedling morphology recognized are considered in relation to the morphology of adult plants and their affinities at specific and sectional level. The distribution of the hydathodes has proved useful in the delimitation of supra-specific taxau ThB morphology of the developing seedlings and the distribution of the hydathodes on the leaves become the main arguments for a new classification in the genus Crassula. A cytological review stresses the different basic chromosome numbers (8,7) and their structural differences for the delimitation of the subgenera. Problems in determining the original basic number and the high percentage of polyploidy with various rainfall conditions are evaluated. Subsequently the characteristics and affinities of Crassula and its subgeneric taxa are briefly discussed. The key to the species, subspecies and varieties is divided into twelve groups which are similar to sections or groups of sections recognized. Within the genus Crassula 2 supgenera, 21 sections, 11 subsections and 144 Southern African species with 124 subspecific taxa are distinguished, described, their variation recorded and their diagnostic features accentuated. Species insufficiently known and excluded are briefly discussed.